Ultrastructure of Escherichia coli cells under the action of a novel derivative of aryl aliphatic aminoalcohols. - Dronova, M. L.; Voychuk, S. I.; Vrynchanu, N. O. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Novel derivatives of aryl aliphatic aminoalcohols were examined for antimicrobial activity. Compound KVM-114 (4-(1,1,3,3-tetrabutyl) phenoxy-3-dimethylamino-2-propanol hydrochloride) was found as a selective against gram-negative bacteria. Objective. Investigation of compound KVM-114 influence on E. coli ultrastructure. Methods. Minimum inhibitory concentrations were determined by serial dilution method in Muller-Hinton broth. Bacteria (Escherichia coli) for transmission electron microscopy samples preparation was grown to exponential phase and then was exposed to the subinhibitory concentration of KVM-114 for 1 h and 24 h. Results. Intact E. coli cells were rod-shaped with rounded ends. A light layer, allowing clear visualization of the cell wall, was observed between the сytoplasm and cytoplasmic membrane. Lipopolysaccharide layer was well distinguished as well. Cytoplasm was filled with ribosomes and polyribosomes. 1 hour exposition to KVM-114 at a subinhibitory concentration resulted in the absence of polyribosomes in the cytoplasm. Increase of electron density of lipopolysaccharide layer and cell wall indicate alteration of cell envelope. Prolongation of the incubation period to 24 hours led to cell recovery: no changes were observed, compared to control cells. The data obtained suggest compound’s ability to alter cell envelope and metabolic activity, however, subinhibitory concentration is apparently not sufficient for total inhibition of E. coli growth. Conclusion. The derivative of aryl aliphatic aminoalcohols, compound KVM-114, possesses inhibitory activity against gram-negative bacteria. E. coli treatment with this compound resulted in structural changes of the cell wall and alteration of intracellular processes.